Teen Birth Rates Decline - Suzanna Smith (EDIS)
“Parents and others who are concerned about teenagers having babies have reason to celebrate. According to the nonprofit research organization Child Trends, the teenage birth rate for 15-19 year olds is at the lowest point in over 40 years. This drop began in 1991 and has receded steadily so that it is now one-third lower than the 1991 peak. The other good news is that it continues to fall.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, July 2012.